A ranking of critical competencies for maritime logistics executives in the era of digitalisation - Ng, Charlene Xin Ying (Nanyang Technological University, 2021)
The rapid pace of globalisation and digitalisation in the world causes a need for the society to continuously reinvent themselves. This applies true for organisations and how they should consistently review the competency requirements of their employees so to achieve the highest performance and efficiency in the era of digitalisation. This paper focuses on reviewing and updating the competencies maritime logistics executives (MLEs) in the era of digitalisation. Numerous research over the last two decades have shown a variety of updated or integrated frameworks based on the BLM (Business, Logistics and Management) model, but they have yet to present one that emphasises on rising trends such as digitalisation, geopolitics, and sustainability. Hence, this paper closes the research gap by identifying and ranking the key competencies required by MLEs in an era of digitalisation by utilising a theory-driven method. Firstly, the key and sub-competencies were identified and structured into a BLMD (Business, Logistics, Management, Digitalisation) competency framework after factoring in emerging trends and the existing literature. The key competencies were then finalised as Business skills, Logistics skills, Management skills, and Digitalisation skills, and with its associated 18 sub-competencies. A total of 363 maritime logistics related companies were approached to complete a questionnaire that was structured and reviewed, to which 51 responses were collected. The data collected was analysed using the fuzzy analytic hierarchy process (FAHP). The findings found that the key competencies were ranked, from most to least importance, as such: Business skills, Logistics skills, Management skills, and Digitalisation skills. The results of this study show a difference between senior and management level executives and non-management executives, as well as a possible shift in perspective of the required competencies from Management skills to Business skills. The sub-competency Leadership and Managerial Abilities was ranked top five globally in importance, showing that this sub-competency is important regardless of position in the organisation. The results also further emphasised the slow speed of digitalisation in the shipping industry as Digitalisation skills was ranked last in importance despite the transition into a digital era across the globe. Hence, candidates with good general knowledge on current events and business operations while having sufficient multimodal transport and distribution knowledge and leadership skills should be prioritised when hiring and upgrading employees to achieve the best performance in a maritime logistics company. This paper also further recommended the research of social capital as a complement to the current study of human capital on MLEs.